A CWDM/DWDM arrayed waveguide grating based on photodefinable polymer - Ibrahim, M. H.; Kassim, N. M.; Mohammad, Abu Bakar; Ismahayati, Adam (Institutul National de Cercetare-Dezvoltare pentru Optoelectronica, 2010)
Link to publisher's homepage at http://inoe.inoe.ro/